The impact of corporate social responsibility on the Peruvian consumer’s purchasing behavior - Guerrero, Giuliana (2015)
This exploratory research aims to find out the extent to which Corporate Social Responsibility (CSR) impacts the purchasing behavior of Peruvian consumers when it comes to convenience food products. The study includes qualitative and quantitative analysis. Qualitative analysis consists of in-depth interviews with CSR representatives from consumer product companies, CSR practitioners and some consumers from the quantitative sample. That group’s composition was selected in order to obtain a wide picture of the consumers’ perception towards CSR, including their understanding of the concept and the relevance in their decision making process when buying convenience food products. The quantitative analysis portion consists of an on-line survey focused on Peruvian consumers who live in Lima during the year 2015. Consumers included in the sample were selected by convenience. After analyzing the 134 completed surveys, the results obtained suggest that even though there is an increasing interest in CSR, including CSR as an attribute of the purchased goods, interest is not fully demonstrated by the purchasing behavior of consumers. The main breach leading to this inconsistency appears to be the lack of or failure in the companies’ CSR communication towards consumers. Consumers demand reliable information which socially responsible companies usually provide; however at this stage, the target audiences of such information are mostly corporations and communities surrounding the manufacturing plants of convenience food products.